Spirituality, Fan Culture, and the Music of Jerry Joseph & the Jackmormons. (26th May 2016) - Harmon, Justin T.; Dox, Donnalee
ABSTRACT: This article presents findings from a qualitative study with passionate fans of the rock and roll band, Jerry Joseph & the Jackmormons. The study looked at how fan involvement in the music scene enhanced quality of life through the ability to access a personal sense of spirituality. While the majority of participants (87%) had been raised in religious households, most of those (93%) had intentionally abandoned religious affiliation only to come to embrace a language of spirituality and religion to describe their attraction to the music. This study fills a gap by exploring how aspects of spiritual language and sensations can be embraced in a secular context after departure from a formal religious upbringing.